A functionalist approach to the paradox of the simplistic and faithful translation of B2C webpages for banking products of the four systemic banks of Greece - (:unkn) unknown (My University, 2021)
This dissertation looks into why the English translation of the webpages of the main B2C banking products as presented by the four systemic banks of Greece in their respective websites is rather simplistic compared to their corporate webpages. A hypothesis is formed that the translation is kept simple and close to the original because it is addressed to non-native English speakers in Greece. In an attempt to explain this paradox and to test this hypothesis, the paper draws upon the “skopos” translation theory, the audience design theory and associated concepts, also proceeding to brief comparisons with B2C product webpages of other sectors
Keywords: Θεωρία σκοπού, Νορντ; Functionalist approach, Nord, Skopos theory, audience design theory, ELF